Pelatihan Pembuatan Jamu Instan Berbasis Home Industry Kader Puskesmas Perumnas 2 di Kelurahan Sei Beliung Kota Pontianak - Husnani Husnani; Heny Puspa Sari; Wilda Wildaniah (Al-Khidmah, 2019)
Perumnas 2 Community Health Center cadre is one of the women's organizations in Sei Beliung Village of Pontianak City. The educational backgrounds of the PKK mothers are diverse (high school graduates and universities), and most are housewives with family economic conditions that are in the middle to lower economy. Finding work is increasingly difficult for these mothers, while the need for sufficient daily necessities requires increased expenditure. Whenever, there are believe that they have many abilities to improving family welfare. Empowerment of Community Health Center cadre as members of the community and still classified as productive workforce is very important to do, with aiming to foster awareness and independence in business, while expanding employment to increase family income in an effort to achieve a happy and prosperous family. In relation to efforts to foster and develop the potential of families and regions, it can be done through various alternative activities, including training in making Instant Herbs from gingger, ginger and turmeric. This guidance is expected to be able to complement the insights of the knowledge and skills of Community Health Center cadre in various aspects of family life, which can be used to demonstrate their existence, help fulfill their family's needs so that doing it alone saves family finances and can be used as a business increase family income.